Monetary policy announcements and sacrifice ratios - Gene Ambrocio; Markus Haavio; Nigel McClung (Bank of Finland, 2024)
We show that sacrifice ratios associated with announcements of the most likely course of monetary policy are lower when the implementation date is further out into the future in the basic New Keynesian framework. This is not due to forward guidance puzzle effects and holds even when agents' expectations feature cognitive discounting. Nevertheless, the rate at which sacrifice ratios fall with the implementation horizon is attenuated by the intensity of cognitive discounting. We also show that our results also hold in a model with additional real and nominal rigidities. These results indicate that telegraphing the most likely course of action for monetary policy attenuates the effects on output relative to inflation.
urn:nbn:fi-fe2024111190790
Keywords: E31; E52; E58; 330; monetary policy announcements; sacrifice ratio; cognitive discounting